HISTORY AND FACTORS OF MISSIONARY MOVEMENTS IN WORLD RELIGIONS - Jasur Najmitdinov (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article analyzes historical, theoretical and scriptural bases of missionary work in Buddhism, Christianity, and Islam, which are classified as World Religions. In particular, significance of early Buddhist missions, social, and political factors that influenced the spread of classical Buddhism and its modern forms as Lamaism and Zen Buddhism throughout the world is examined. Also, it is stated that Christianity is considered as most active missionary religion, has passed through seven stages in its history. In addition, it is argued that Islamic missionary or da’wah happened in parallel of Islamic conquests, activity of Muslim traders and hermits (sufis).